2017
DOI: 10.1111/scs.12554
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional descriptive study of the family functioning, health and social support of hospital patients with family violence backgrounds

Abstract: Family violence (FV) has serious effects on the health and well-being of the family. The health sector plays a vital role in FV prevention by helping to identify abuse early, providing victims with the necessary treatment and referring patients to appropriate care. The aim of the present cross-sectional study was to describe the prevalence of FV among hospital patients, as well as to assess the association between family functioning, health and social support, considering patients as the perpetrators or victim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It is particularly alarming, since the costs can only be rising as domestic violence increases and continues in the aftereffects of the COVID-19 pandemic. It has been shown that the prevention and early intervention of domestic violence is a comprehensive and profitable investment for the society, where the health care professionals have an important role to play [2] , [7] , [9] . Especially, the sexual and reproductive health sector, which most women will access at some point in their lives, have an excellent option to deal with domestic violence.…”
mentioning
confidence: 99%
“…It is particularly alarming, since the costs can only be rising as domestic violence increases and continues in the aftereffects of the COVID-19 pandemic. It has been shown that the prevention and early intervention of domestic violence is a comprehensive and profitable investment for the society, where the health care professionals have an important role to play [2] , [7] , [9] . Especially, the sexual and reproductive health sector, which most women will access at some point in their lives, have an excellent option to deal with domestic violence.…”
mentioning
confidence: 99%
“…IPV is a significant problem not often identified by health services. Both men and women experience violence, but few seek help from healthcare professionals (Kivelä et al 2018). Previous studies have shown that victims and perpetrators with violent experiences have more hospital visits, several diagnoses, mismatches between reports, and a higher rate of readmission than patients who have not experienced violence (Chan et al 2013;Matteoli et al 2016).…”
mentioning
confidence: 99%